1993
DOI: 10.3171/jns.1993.78.1.0005
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome in patients with surgically treated cerebral arteriovenous malformations

Abstract: A series of 280 cases of cerebral arteriovenous malformations (AVM's) treated surgically between June, 1970, and June, 1989, is reviewed with particular focus on the preoperative seizure history and follow-up seizure status. Follow-up evaluation (mean duration 7.5 years) was achieved in 98% of cases and was accomplished through re-examinations, telephone interviews, and written questionnaires. Overall, 89% of the surviving patients with a follow-up period of greater than 2 years were free of seizures at last e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(62 citation statements)
references
References 19 publications
4
54
2
1
Order By: Relevance
“…6 Previous studies have indicated a higher risk for seizures in male patients, in patients with AVMs larger than 3 cm, in younger (< 18 years) patients, and in patients with superficial venous outflow drainage from a temporal lobe location. 10,12,17,18,31,39 Our study also found that males had a higher likelihood of seizure activity and that seizures were less common in younger patients, especially those younger than 18 years. Of interest, we also found that seizures were less common in patients who had sustained an intracranial hemorrhage.…”
Section: Factors Associated With Seizuressupporting
confidence: 61%
“…6 Previous studies have indicated a higher risk for seizures in male patients, in patients with AVMs larger than 3 cm, in younger (< 18 years) patients, and in patients with superficial venous outflow drainage from a temporal lobe location. 10,12,17,18,31,39 Our study also found that males had a higher likelihood of seizure activity and that seizures were less common in younger patients, especially those younger than 18 years. Of interest, we also found that seizures were less common in patients who had sustained an intracranial hemorrhage.…”
Section: Factors Associated With Seizuressupporting
confidence: 61%
“…Additionally, these surgically induced seizures may become progressively more intractable. 49,52,66 The reported risk of new-onset seizures after microsurgical resection varies widely, ranging from 3% to 32%. 1,19,29,33,52,66 In contrast, SRS appears to confer a lower seizure risk for patients without pretreatment seizures, with rates ranging from 0% to 7%.…”
mentioning
confidence: 99%
“…49,52,66 The reported risk of new-onset seizures after microsurgical resection varies widely, ranging from 3% to 32%. 1,19,29,33,52,66 In contrast, SRS appears to confer a lower seizure risk for patients without pretreatment seizures, with rates ranging from 0% to 7%. 5,33,69 Current treatment options offer relatively effective seizure control with modality-specific risks and complications.…”
mentioning
confidence: 99%
“…29,30 Some reports [31][32][33] suggest that BAVM surgery allows good control of the seizure disorder. Treatment of such malformations is supposed to decrease the spontaneous risk associated with the malformation and/or cure the symptoms.…”
mentioning
confidence: 99%